Enhancing Catfish (Clarias sp.) Farming Production and Economic Viability through Molasses Application in Biofloc System - Deni Aulia; Bambang Suprakto; Budimawan Budimawan; Angkasa Putra; Sarifah Aini; Ruzkiah Asaf; Sri Wartini; Nunung Sabariyah (Depik, 2024)
In addition to having high economic value, catfish (Clarias sp.) can also be cultivated quickly and they can adapt well. The demand of catfish is in line with the increase in production which is expected to remain efficient and environmentally sound. Biofloc technology has also been implemented in catfish for increasing productivity. Biofloc utilizes the activity of heterotrophic microorganisms and autotrophs for the conversion of organic waste into floc and is used as fish feed. This study aims to examine the effect of the use of molasses with different doses (C/N ratio) on the growth and survival rate of catfish. This study was conducted with as many as 3 treatments with 3 repetitions each except for the control. The treatment with the ratio of molasses in each of them: A: C/N of 10:1; B: C/N of 15:1; C: C/N of 20:1, and D without molasses given as control. The study using 240 catfish measuring 10-12 cm was carried out for 30 days with sampling every 10 days. It aims to determine the average growth, daily growth, and survival rate of test biota during the study. Based on the results of this study, it can be concluded that the use of different doses of molasses in catfish farming, and biofloc technology will affect the growth and survival rate of farmed catfish. Catfish farmed with biofloc technology at a C/N ratio of 15:1 show the best results on their growth and survival rate. In addition, catfish farming with a biofloc C/N ratio of 15:1 has a better economic analysis when compared to conventional catfish farming. In summary, the use of biofloc based on research results can be a recommendation to be applied in the community, especially among catfish farmers.